ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL BERDASARKAN TEORI POLYA - Naning Kurniawati; Awawin Mustana Rohmah; Suwito (Journal of Mathematics Education and Science, 2021)
This research is motivated by the many mistakes of students in solving math problems, especially math problems in the form of stories. The student's ability to understand the story problem is determined by the student's verbal ability. Verbal ability is the ability to understand word relationships, vocabulary and quickly accept certain words, including remembering words and patterns to form them. Other causes that cause errors in solving math problems are lack of understanding of the questions, less attention to writing symbols and operations, and the absence of writing conclusions. This fact is obtained from the results of interviews with mathematics teachers and classroom observations. This study aims to identify mistakes made by students in solving problems, especially questions in the form of stories with Polya's theory. This research was conducted at one of the MTs in Dander District, Bojonegoro Regency. The research was carried out on three students who had gone through the selection. Students who are selected to be research subjects are students with low, medium, and high categories. This type of research is a qualitative descriptive study with a case study approach. The subjects of this study were several students at seventh-grade level who had passed selection according to the research objectives in 2020. The data collection method was carried out through essay tests and interview tests. The results showed that the students made six mistakes: not understanding the question, choosing the wrong strategy, not paying attention to the amount or unit, not being right in the calculation, not making the correct conclusion, and not making any conclusions. Abstrak Penelitian ini dilatarbelakangi oleh banyaknya kesalahan siswa dalam menyelesaikan soal matematika khususnya soal matematika dalam bentuk cerita. Kemampuan siswa dalam memahami soal cerita di tentukan oleh kemampuan verbal siswa. Kemampuan verbal merupakan  kemampuan untuk memahami hubungan kata, kosakata serta menerima dengan cepat kata-kata tertentu termasuk kemampuan mengingat kata-kata dan pola membentuknya. Penyebab lain yang menyebabkan kesalahan dalam menyelesaikan soal matematika yaitu kurang memahami pertanyaan pada soal, kurang memperhatikan penulisan simbol dan operasi serta tidak adanya penulisan kesimpulan. Fakta ini diperoleh dari hasil wawancara dengan guru matematika dan pengamatan dikelas. Penelitian ini bertujuan untuk mengidentifikasi kesalahan yang dilakukan siswa dalam menyelesaikan soal khususnya soal berbentuk cerita dengan teori Polya. Penelitian ini dilaksanakan di salah satu MTs di Kecamatan Dander Kabupaten Bojonegoro. Penelitian dilaksanakan kepada 3 siswa yang telah melalui seleksi. Siswa yang terpilih untuk dijadikan subjek penelitian adalah siswa dengan kategori rendah, sedang dan tinggi. Jenis penelitian ini adalah penelitian deskriptif kualitatif dengan pendekatan studi kasus. Subjek penelitian ini adalah beberapa siswa di jenjang kelas VII yang telah melewati seleksi sesuai tujuan peneliti pada tahun 2020. Metode pengumpulan data dilaksanakan melalui tes essay dan tes wawancara. Hasil penelitian menunjukkan bahwa ada enam kesalahan yang dilakukan siswa yaitu tidak memahami pertanyaan, pemilihan strategi yang tidak tepat, tidak memperhatikan besaran atau satuan, tidak tepat dalam perhitungan, tidak tepat dalam menarik kesimpulan dan tidak adanya kesimpulan yang diberikan.